Solar semi-diurnal variation of Pressure - JAGANNATHAN, P.; ALVI, S. M. A. (MAUSAM, 1964)
A statistical study has been made of the year to year variation of solar semidiurnal wave of atmospheric pressure over Delhi for the period 1948-1960. It has been found that there has been a slight decrease of amplitude during the period 1954-1960 as compared with the previous period. There has also been a tendency for positive anomalies and the negative anomalies longer than two months to persist. These have been compared with the results of & similar study of Singapore.